Sheet and network based functionally graded lattice structures manufactured by selective laser melting: Design, mechanical properties, and simulation. (1st June 2020) - Zhou, Hailun; Zhao, Miao; Ma, Zhibo; Zhang, David Z.; Fu, Guang
Highlight: Design method of sheet based functionally graded Gyroid structure based on the mathematical expression of triply periodic minimal surfaces. Sheet based functionally graded Gyroid exhibited failure mechanism of layer-by-layer buckling deformation. Superior energy absorption capability of sheet based functionally graded Gyroid structure. The Johnson-Cook models were implemented to simulate the deformation response of the lattice structures. Abstract: The triply periodic minimal surfaces (TPMS) have caught a lot of attention to many applications recently such as biomaterials, lightweight components with high strength and functionally graded material (FGM). In this study, the designing methods of the network based functionally graded Gyroid (N-FGG) and sheet based functionally graded Gyroid (S-FGG) structures were presented. The specimens of N-FGG and S-FGG based structures were fabricated by selective laser melting (SLM) with Ti-6Al-4V powder, then followed by quasi-static compression tests to measure the mechanical properties. The S-FGG based structure showed higher elastic modulus, yield strength and more stable stress fluctuation than N-FGG based structure with the same range of volume fraction gradient. The dominated deformation behaviors of both graded lattice structures were layer-by-layer. However, the S-FGG based structure showed more of buckling failure while the N-FGG based structure exhibited more of brittle fracture. Furthermore, the finite element analysis (FEA) with the Johnson-Cook plastic and damage models was implemented to simulate the plastic deformation and the failure behavior of the lattice materials at the post-yield stages. The simulated results illustrated that the compressive stress concentrated in the middle area of struts which connected the two adjacent layers of N-FGG based structures, while the stress in S-FGG based structures was distributed much uniformly in the middle connection region. S-FGG based structure also showed higher ultimate stress with the increase of compressive strain. Finally, the energy absorption capability of lattice structures was investigated, and the results indicated that the S-FGG based structure showed more total energy absorption per unit volume and higher energy efficiency, which means good prospects especially in the applications of relatively high allowable stress. Graphic abstract: Image, graphical abstract